Enzymatic diagnosis of neuronal lipofuscinoses in dried blood spots using substrates for concomitant tandem mass spectrometry and fluorimetry. (13th December 2020) - Maeser, Stefan; Petre, Brindusa‐Alina; Ion, Laura; Rawer, Stephan; Kohlschütter, Alfried; Santorelli, Filippo M.; Simonati, Alessandro; Schulz, Angela; Przybylski, Michael
Abstract: Neuronal ceroid lipofuscinoses (NCLs) are a group of neurodegenerative diseases predominantly in childhood that are characterized by psychomotor deterioration, epilepsy, and early death of patients. The NCLs analyzed in the present study are caused by defects of the specific enzymes, CLN1 (palmitoyl protein thioesterase 1; PPT1), CLN2 (tripeptidyl peptidase 1; TPP1), and CLN10 (cathepsin D). Specific and sensitive diagnostic assays of NCLs were the main goal of this study. They are of increasing importance, particularly since enzyme replacement therapy (ERT) for NCL2 has recently become available for clinical treatment, and ERTs for further NCLs are under development. Here, we report specific and sensitive determinations for CLN1, CLN2, and CLN10 on dried blood spots by tandem mass spectrometry using multiple reaction monitoring mass spectrometry (MRM‐MS). Identical substrates suitable for (i) fluorimetric determination of single enzymes and (ii) for MRM‐MS determination of multiple enzymes were synthesized by chemical coupling of alkyl‐umbelliferone building blocks with the corresponding peptidyl‐substrate groups recognized by the target enzyme. Enzymatic determinations were performed both by fluorimetry and MRM‐MS in patients with NCL1, NCL2, and NCL10 and showed good agreement in single assays. Moreover, duplex and triplex determinations were successfully performed for NCL1, NCL2, and NCL10. Specific peptidyl‐(4‐alkyl‐umbelliferone) substrates were also synthesized for mass spectrometric determinations of different cathepsins (cathepsins‐D, ‐F, and ‐B), to provide a differentiation of proteolytic specificities.